The Act of Digression In Academic Novels: - (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Onecannot go to the novel expecting a series of events connected withacademicians, it is a psychological novel dealing with a psychic personalitywho happens to be a student. Holden is sent out of three institutions becausehe does not want to be a "phony," by habitually or constantly abidingby the rules and regulations. What he aspires for is being true to his ownfeelings at a particular pointof time. Further his opinions and judgements are always in a state of flux. Butbecause of this unsettling sense of the flux of things there has developedwithin Holden a compensatory desire for permanence. That is why he loves themuseum where everything is what it was when he was a young boy. He says themuseum is "the only nice dry, cozy place in the world" (C.I.R: 120).